ANALISIS PERAN AKTOR DALAM PEMEKARAN KABUPATEN BREBES - Trisnawati, Akhpriyani; ., Fitriyah; Setiyono, Budi (Journal of Politic and Government Studies, 2015)
ABSTRACTIONOpportunities of the policy about the expansion which protected by UU No. 32 of 2004 article 4-8 and PP No. 78 of 2007 made a lot of local and regional elites take an advantage of these opportunities, as well as the southern of Brebes region. The expansion discourse that several years dim come back arise after the election 2012. Although, the pros and contras coloring of the expansion discourse in brebes regency, but the expansion cannot be happened without the actors role to achieve expansion. Therefore, the formulation of the problem in this this research is